Preliminary Study on Corruption Case in the Indonesian Banking Sector: Overview of the Fraudster, Loss, and Fraud Modes - Windhu Wibisono (Association of Certified Fraud Examiners Indonesia Chapter, 2023)
The banking sector is the area with the most corruption on a global and national scale (ACFE, 2021; ACFE Indonesia Chapter, 2020). The banking sector itself is a sector that is rigid in terms of regulation and places great emphasis on prudential aspects in its business processes. Bahoo (2020) in his paper states that corruption in the banking sector raises considerations for building an anti-corruption architectural system within banks to eradicate corruption. This preliminary study will describe cases of corruption in the banking sector in Indonesia in a limited period of time. This study uses data from court rulings related to banking corruption cases registered in 2020. The overview of corruption cases shows the central tendency related to the profile of fraudsters, the value of state finance loss, court imprisonment, and the modus operandi of fraud/corruption committed by the perpetrators. The findings show that corruption in the banking sector in Indonesia occurs at State-Owned Enterprises and Local Government-Owned in the form of commercial banks, rural banks and sharia rural banks. The data indicates that in terms of gender, the fraudsters, although still dominated by the male gender, are relatively equal with the female gender where ratio of the male and the female is 6:4. Furthermore, the data indicates that in terms of position or rank of the fraudster, the higher the position of the bank’s internal employee, the greater the value of state finance loss incurred. The results of this study also show that the modus operandi of crimes that often occur is borrowing the name of the debtor, fictitious credit, and collusion in applying for credit. The repeated modus operandi is a challenge for policy managers in designing better systems and governance to eliminate the level of corruption in the banking sector. In the future, it is necessary to expand and enrich data collection and data analysis of corruption cases in the banking sector in Indonesia so that it can provide a better picture.